Stability Charts for Pseudostatic Stability Analysis of Rock Slopes Using the Nonlinear Hoek–Brown Strength Reduction Technique. (6th August 2020) - Sun, Chaowei; Chai, Junrui; Luo, Tao; Xu, Zengguang; Qin, Yuan; Yuan, Xiaosa; Ma, Bin
Abstract : This paper presents a set of stability charts for the stability assessment of rock slopes that satisfy the Hoek–Brown (HB) criterion under various seismic loading conditions. The nonlinear Hoek–Brown strength reduction technique is used to conduct pseudostatic stability analysis of rock slopes subjected to horizontal seismic excitation. Based on an extensive parametric study, first, a set of stability charts with a slope angle of β  = 45° under static and pseudostatic conditions are proposed by using ABAQUS 6.10 software. Second, the slope angle weighting factor ( f β ) and the seismic weighting factor ( f kh ) are adopted to characterize the influence of slope angle ( β ) and horizontal seismic acceleration coefficient ( k h ) on the rock slope stability. Finally, the reliability of the proposed charts was validated by three typical examples and two case studies, and the results show that the values of the factor of safety (FOS) obtained from the proposed charts are consistent with the values from other methods. The proposed charts provide an efficient and convenient way to determine the FOS of rock slopes directly from the rock mass properties ( γ and σ ci ), the HB parameters ( m i and GSI), the slope geometry ( H and β ), and the horizontal seismic coefficients ( k h ).